RETRACTED: Dynamics of plants and non-quarantine organisms internal quarantine objects spread - Khayrullayev Muhriddin; Rajabova Gulkhayo (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001